An exploration of natural science teachers' experiences and perceptions of the National Standardised Achievement Tests : a case study - Shaakumeni, Simson Ndadaleka (Rhodes University, Faculty of Education, Department of Education, 2013)
The primary purpose of this study was to capture Natural Science teachers' perceptions of the national standardised achievement tests (SATs), with a view to illuminating whether or not they were able to interpret and use the SATs reports to inform their practice and for improvement purposes as envisaged in the standardised tests' objectives. It further sought to investigate how the grade 7 Natural Science teachers were teaching the subject matter, with a view to understanding the performance of learners as illustrated in the 2010 SATs results. The study mainly used qualitative methods such as observations, interviews and document analysis. These were complemented by quantitative methods through the use of the questionnaires, which were used to capture the general perceptions and experiences of Natural Science teachers. Thirty-five questionnaires were sent out and ten responses were received. Quantitative data from the questionnaires were analysed by tabulation to ascertain the frequencies of responses regarding teachers' perceptions and experiences of SATs, as indicated in different scales per indicator. Furthermore, data generated through video-taped lessons, analysis of learners' written notes, interviews and open-ended questions from the questionnaires were inductively analyzed. The findings of the study revealed that teachers had positive perceptions towards the ideals of SATs. However, their use of the SATs reports in their teaching was inconclusive. The study also revealed that there were no policy imperatives on SATs, in particular, to guide their use in schools. It was also found that teachers were not teaching the syllabus competencies fully and their Natural Science content knowledge was inadequate. The principal recommendation is that teachers need to acquaint themselves sufficiently with the SATs reports to enable them to use the reports for their intended purposes. Furthermore, teachers need to engage in continuous professional development programmes to improve their Natural Science content knowledge, especially with regard to making information in the textbooks accessible to learners in terms of addressing competencies in the syllabus. Finally, there is a need for policy intervention from the Ministry of Education in Namibia so that the existing tensions between policy formulation and implementation are addressed.
Keywords: Achievement tests -- Education (Elementary) -- Research -- Namibia; Educational tests and measurements -- Research -- Namibia; Educational tests and measurements -- Research -- Namibia; Science -- Study and teaching (Elementary) -- Namibia; Science teachers -- Namibia; Education, Elementary -- Standards -- Research -- Namibia